The effectiveness of the use of augmented reality-assisted physics e-module based on pedicab to improve mathematical communication and critical thinking abilities - Poppy Sari Dewi; Heru Kuswanto (OmniaScience, 2023)
This study aims to reveal the effectiveness of the use of an augmented reality-assisted physics e-module based on the local wisdom of the pedicab in improving critical thinking and mathematical communication abilities. The study used the 4D model. Empirical trials were conducted involving 255 grade XII students. The effectiveness test was conducted in class X with 36 students as the experimental class and 36 students as the control class at SMA Negeri 1 Depok, Sleman. The data analysis used the Quest program to see the validity and reliability of the items, and the Manova test (effect size) was carried out to see the effectiveness of the media. The results showed that the augmented reality-assisted physics e-module based on the local wisdom of pedicab was effective in improving mathematical communication with a score of 0.40 (large) and critical thinking abilities with a score 0.11 (medium).